Combined analysis of transcriptome and WGCNA reveals the mediating role of JA in the low male fertility of loquat H30-6 - Wang, Junxiu; Pan, Jinting; Xia, Qingqing; Duan, Yudie; Jing, Danlong; Dang, Jiangbo; Guo, Qigao (Frontiers in Plant Science, 2025)
The number of seeds is an important factor limiting the palatability and processing efficiency of loquat. Loquat H30-6 has been found to bear fruits with few seeds, which is attributed to its low male fertility. To investigate the molecular mechanism underlying the low male fertility of H30-6, in this study, RNA-seq was performed using pre-meiotic, meiotic and mature anthers from H30-6 and the other two loquat varieties with normal male fertility. The results indicated that a total of 331 differentially expressed genes (DEGs) were identified between H30-6 and the other two loquats and these DEGs were mainly enriched in pathways related to jasmonic acid (JA). WGCNA revealed that module ‘green’ were highly positively correlated with seed quantity (r = 0.46), suggesting that module ‘green’ is the candidate module. Enrichment analysis showed that genes in module ‘green’ were also primarily enriched in JA biosynthetic process, regulation of JA mediated signaling pathway and response to JA, implying that JA may play a key role in the molecular mechanism underlying the low male fertility of H30-6. The detection of UPLC-MS/MS indicated that the contents of JA and its derivatives in the flower bud of H30-6 were significantly lower than those in ‘Huabai 1’ (with normal male fertility). Besides, exogenous application of MeJA improved the pollen quantity per anther and seed numbers of H30-6. Our work indicates that the suppression of JA-related gene expression and the low JA content in immature flower buds may be key factors for H30-6 male sterility. These findings provide a theoretical basis for seedless breeding of loquats and lay the foundation for the development of stamens in fruit trees.